Unified theory of firm: an empirical analysis - Duasa, Jarita; Sarif, Suhaimi Mhd; Abdul Sabian, Nur Arfifah (Emerald Publishing, 2020)
Purpose – Four main strategies required for firms to be able to achieve their main objectives in organizations under the unified theory of the firm are technological advance, intellectual development, spirituality conducts and customer satisfaction concern. This study aims to explore the inclination of firms to adopt all these strategies in, factors that contribute to the adoption of all these strategies and significant relationship between these strategies of firms in the context of Malaysian firms. Design/methodology/approach – Using primary data from the survey on a sample of firms in the financial sector of Malaysia, the study adopts several methods of analysis such as t-test for dependent sample, t-test for independent sample and correlation. Furthermore, ordinary least squares regressions are estimated to determine factors that have an impact on a particular strategy. Findings – It is found that the strategies of the unified theory of the firm significantly contributed to the education level of managers. Highly educated managers tend to adopt strategies most of the time. It is also found that scores of customer satisfaction concern are highly related to scores of intellectual development and spirituality conduct. The correlation coefficient is also high between spirituality conduct and intellectual development. Originality/value – The study analyzes the adoption of important strategies of a unified theory of firm among several firms using first-hand data (primary data) collected from the survey